Assessment of Different Remote Sensing Data for Forest Structural Attributes Estimation in the Hyrcanian forests - Noureddin Nourian; Shaban Shataee-Joibary; Jahangir Mohammadi (Forest Systems, 2016)
Aim of study: The objective of the study was the comparative assessment of various spatial resolutions of optical satellite imagery including Landsat-TM, ASTER, and Quickbird data to estimate the forest structure attributes of Hyrcanian forests, Golestan province, northernIran.